Safety of neoadjuvant chemotherapy in patients with muscle‐invasive bladder cancer and malignant ureteric obstruction. (26th April 2021) - Strother, Marshall C.; Kutikov, Alexander; Epstein, Matthew; Bochner, Emily; Deng, Mengying; Handorf, Elizabeth; Lewis, Bianca; Ghatalia, Pooja; Greenberg, Richard E.; Chen, David; Viterbo, Rosalia; Anari, Fern; et al.
Abstract : Objectives: To determine whether patients with carcinoma invading bladder muscle (MIBC) and ureteric obstruction can safely receive cisplatin‐based neoadjuvant chemotherapy (C‐NAC), and to determine whether such patients require relief of obstruction with a ureteric stent or percutaneous nephrostomy prior to beginning C‐NAC. Patients and Methods: We performed a single‐institution retrospective analysis of MIBC patients receiving C‐NAC and falling into three groups: no ureteric obstruction (NO); relieved ureteric obstruction (RO); and unrelieved ureteric obstruction (URO). To address whether patients with obstruction can safely receive C‐NAC, we compared patients with NO to those with RO, with the primary outcome of premature chemotherapy discontinuation. To investigate whether patients with obstruction should have the obstruction relieved prior to NAC, we compared RO to URO patients using a primary composite outcome of grade ≥ 3 adverse events, premature chemotherapy discontinuation, dose reduction, or dose interruption. The primary outcomes were compared using multivariable logistic regression. Sensitivity analyses were performed for the RO vs URO comparison, in which patients with only mild degrees of obstruction were excluded from the URO group. Results: A total of 193 patients with NO, 49 with RO, and 35 with URO were analysed. There were no statistically significant differences between those with NO and those with RO in chemotherapy discontinuation (15% vs 22%; P = 0.3) or any secondary outcome. There was no statistically significant difference between those with RO and URO in the primary composite outcome (51% vs 53%; P = 1) or any secondary outcome. Conclusion: Patients with ureteric obstruction can safely receive C‐NAC. Relief of obstruction was not associated with increased safety of C‐NAC delivery.